ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA CV. YAZID BERSAUDARA FARM PERIODE TAHUN 2019-2021 (JAPB, 2022)
This study aims to determine the analysis of financial statements in order to measure financial performance at CV. Yazid Brothers Farm for the 2019-2021 period. The data analysis technique in this study is quantitative research, applying a quantitative approach, namely by applying financial reports to assess financial performance by using the calculation of financial ratios, namely liquidity ratios, solvency ratios, profitability ratios and activity ratios. The results of this study indicate that the industry standard for the liquidity ratio (current ratio) is 263.73% which is above 200% of the industry average so that it is categorized as healthy. Meanwhile (quick ratio) of 23.84% which is below 150% of the industry average so that it is categorized as unhealthy. In the solvency ratio (debt to equity ratio of 19.24% which is below 90% of the industry average and debt to asset ratio of 15.91% which is below 35% of the industry average) so that it is categorized as unhealthy . In the profitability ratio (net profit margin of 3.29% which is below 20% of the industry average, return on assets is 2.35% which is below 30% of the industry average and Return on equity is 2, 84% which is below 40% of the industry average) so it is categorized as unhealthy. The activity ratio (total asset turnover) is 2.87 times which is above 2 times the industry average so it is categorized as healthy. Meanwhile (fixed asset turnover) is 4.56 times which is below 5 times the industry average so it is categorized as unhealthy. Keywords: Financial Statements and Financial Performance.